Photovoltaic energy storage high-voltage wiring harness with flame retardant performance and preparation method thereof

By using polyvinyl chloride resin and polydopamine-coated alumina/silicon nitride material, the insulating layer of photovoltaic energy storage high-voltage wire harness is prepared, and the problem of insufficient flame retardant performance in the prior art is solved, and excellent insulation, electromagnetic shielding performance and simplified process flow are achieved.

CN118675792BActive Publication Date: 2025-03-18SHENZHEN LONGHUI POWER IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410697942.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-03-18
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The existing photovoltaic energy storage high-voltage wire harnesses have shortcomings in taking into account insulation, electromagnetic shielding performance and flame retardant performance. Especially in applications in high-voltage cables, the flame retardant performance is poor, making it difficult to ensure the improvement of electromagnetic shielding performance and resistivity.

Method used

An insulating layer is prepared by a double-screw extruder granulation process using polyvinyl chloride resin and polydopamine-coated aluminum oxide/silicon nitride material. Combining the advantages of alumina and silicon nitride, a material with excellent insulation and electromagnetic shielding properties is formed.

Benefits of technology

It realizes that while ensuring insulation and electromagnetic shielding performance, the wire harness structure is simplified, the process flow is reduced, and the flame retardant performance of the material is significantly improved. It is suitable for high-voltage wire harnesses for new energy vehicles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of wiring harnesses for new energy vehicles, specifically to a photovoltaic energy storage high-voltage wiring harness with flame retardant properties and a preparation method thereof. The present invention uses silicon nitride, acetamide aluminum hydroxide ionic liquid, and dopamine hydrochloride as raw materials to prepare polydopamine-coated aluminum oxide / silicon nitride with excellent insulation and electromagnetic shielding properties, and applies it to the insulation layer of the high-voltage wiring harness of new energy vehicles. Compared with the traditional structure of two layers of insulation layer and one layer of shielding layer of the high-voltage wiring harness of new energy vehicles, the high-voltage wiring harness prepared by the present invention greatly simplifies the wiring harness structure and reduces the process flow while ensuring insulation and electromagnetic shielding performance, which is the future development direction of high-voltage wiring harnesses for new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy vehicle wiring harnesses, and in particular to a photovoltaic energy storage high-voltage wiring harness with flame retardancy and a preparation method thereof. Background Art

[0002] Photovoltaic energy storage systems and power battery systems usually require high-voltage wire harnesses to connect various components to achieve energy transmission and control signal transmission. The following aspects need to be considered when designing and manufacturing these high-voltage wire harnesses:

[0003] Electrical characteristics: High-voltage wiring harnesses need to be able to withstand high voltage and current in the system while ensuring the reliability and safety of electrical connections. Therefore, the selected wire materials and insulation materials need to have good voltage resistance and arc breakdown resistance.

[0004] Environmental adaptability: Photovoltaic energy storage systems and power battery systems may face various environmental conditions, including high temperature, low temperature, humidity, etc. Therefore, the insulation material of the high-voltage wiring harness needs to have good high temperature resistance, low temperature resistance and humidity resistance to ensure the stable operation of the system.

[0005] Mechanical strength: High-voltage wire harnesses may be subjected to mechanical extrusion, stretching and other forces during installation and use, so they need to have good mechanical strength and wear resistance to prevent damage to the wires and insulation materials.

[0006] Fire resistance: Considering the fire risks that high-voltage wiring harnesses may face, their insulation materials need to have good flame retardant properties to ensure that they will not intensify the fire when a fire occurs and protect the safety of the system.

[0007] Size and layout: The design of the high-voltage wiring harness needs to take into account the layout of the system and the limitations of the installation space to ensure that the size and shape of the wiring harness can adapt to the requirements of the system and can be easily installed and maintained.

[0008] In general, high-voltage wiring harnesses play a vital role in photovoltaic energy storage systems and power battery systems. Their design and manufacturing need to take into account requirements in multiple aspects such as electrical characteristics, environmental adaptability, mechanical strength, and fire resistance to ensure the safe and reliable operation of the system.

[0009] In addition, new energy vehicles are currently developing in the direction of high voltage and high current. Some high-voltage systems withstand voltages as high as 800V and currents as high as 660A. Such large currents and voltages will generate electromagnetic radiation, which will interfere with the normal operation of other electronic components. Therefore, electromagnetic interference must be considered when designing high-voltage wiring harnesses. There are three common ways to shield electromagnetic interference in high-voltage wiring harnesses: (1) the wire has its own shielding layer; (2) adding a shielding sleeve outside the wire; (3) shielding from the source, directly adding a filter to the high-voltage equipment.

[0010] Since fillers with excellent electromagnetic shielding properties have good conductivity, how to achieve the unity of composite material insulation and electromagnetic shielding performance while taking safety into consideration has become a key issue in the development of a new generation of photovoltaic energy storage high-voltage wiring harnesses.

[0011] CN 115612250 A discloses a method for preparing a biomass carbon-based ultra-light insulating electromagnetic shielding material. By designing the critical size of biomass carbon, modulating the core conductivity, and insulating the interface, the material can be integrated with the device matrix, and while generating electromagnetic induction shielding therein, the insulating shell between particles effectively blocks the transport of electrons, forming a higher body resistivity, and ensuring the electrical safety and performance of the surrounding connectors. The defect is that the body resistivity of the carbon-based material itself is low, and it is difficult to increase its resistance while ensuring electromagnetic shielding performance. In addition, its flame retardant performance is poor, and its application in high-voltage cables has great limitations. Summary of the invention

[0012] In view of the deficiencies in the prior art, the present invention provides a photovoltaic energy storage high-voltage wire harness with flame retardant properties and a preparation method thereof.

[0013] A photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises a wire core and an insulating layer.

[0014] The wire core is one of a copper wire and an aluminum alloy wire.

[0015] The insulating layer comprises the following materials:

[0016] Polyvinyl chloride resin;

[0017] Polydopamine coated alumina / silicon nitride.

[0018] Preferably, the photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following raw materials in parts by mass:

[0019] 100 parts of polyvinyl chloride resin;

[0020] Polydopamine coated alumina / silicon nitride 1-10 parts.

[0021] Further preferably, the photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following raw materials in parts by mass:

[0022] 100 parts of polyvinyl chloride resin;

[0023] Polydopamine coated alumina / silicon nitride 1-5 parts.

[0024] The preparation method of the polydopamine-coated aluminum oxide / silicon nitride comprises the following steps:

[0025] S1: mixing acetamide and anhydrous aluminum chloride and stirring until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid;

[0026] S2: adding silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0027] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2 to obtain aluminum oxide / silicon nitride;

[0028] S4: dopamine hydrochloride and water are mixed and stirred until the dopamine hydrochloride is dissolved to obtain a dopamine hydrochloride aqueous solution, and then the aluminum oxide / silicon nitride obtained in step S3 is added, and the pH is adjusted with a tris(hydroxymethyl)aminomethane aqueous solution. Finally, the mixture is stirred, centrifuged, and dried to obtain the polydopamine-coated aluminum oxide / silicon nitride.

[0029] Preferably, the method for preparing the polydopamine-coated aluminum oxide / silicon nitride comprises the following steps:

[0030] S1: Mix 5-10 parts of acetamide and 20-40 parts of anhydrous aluminum chloride by mass, and stir until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid;

[0031] S2, adding 14-28 parts by mass of silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating for 5-10 minutes, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0032] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2, raising the temperature from room temperature to 100-120°C at 1-3°C / min, then raising the temperature to 500-600°C at 10-15°C / min, oxidizing at a constant temperature for 30-60min, and finally cooling naturally to room temperature to obtain aluminum oxide / silicon nitride;

[0033] S4: Mix 1-3 parts of dopamine hydrochloride and 200-400 parts of water by mass and stir until the dopamine hydrochloride is dissolved to obtain an aqueous solution of dopamine hydrochloride, then add 4-8 parts of the aluminum oxide / silicon nitride obtained in step S3, and adjust the pH to 7-9 with a 7-8wt% tris(hydroxymethyl)aminomethane aqueous solution, stir for 20-40 minutes, and finally, centrifuge and dry to obtain the polydopamine-coated aluminum oxide / silicon nitride.

[0034] The ultrasonic frequency is 30-50KHz, and the power is 300-400W.

[0035] The present invention also provides a method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy, comprising the following steps: mixing polyvinyl chloride resin and polydopamine-coated alumina / silicon nitride, placing the mixture in a twin-screw extruder for granulation, and obtaining an insulating layer material; using conventional processes to coat the insulating layer material on the outside of the wire core to form an insulating layer, and obtaining the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0036] The temperature of the feeding zone of the twin-screw extruder is 120-130°C; the temperature of the middle zone is 170-180°C; and the temperature of the discharging zone is 160-170°C.

[0037] The electromagnetic field generated by the high-voltage wires of new energy vehicles is usually high-frequency. This is because in electric vehicles, high-voltage wires are mainly used to connect components such as batteries, motors, inverters, etc., which usually involve the transmission and control of high-frequency AC signals. For example, the motor controller (ECU) will control the speed and torque of the motor in a high-frequency manner, and the inverter will also adjust the conversion of electrical energy in a high-frequency manner. Therefore, the current transmitted by the high-voltage wires between these components is usually high-frequency, and the electromagnetic field generated accordingly is also high-frequency.

[0038] Silicon nitride is a ceramic material with excellent thermal conductivity and mechanical properties, and it has certain potential in high-frequency electromagnetic shielding. Silicon nitride has a high dielectric constant and low dielectric loss, and can effectively absorb and scatter high-frequency electromagnetic waves.

[0039] Alumina is a commonly used ceramic material with excellent mechanical properties and chemical stability. Although the dielectric constant of alumina is relatively low, it can still be used for high-frequency electromagnetic shielding, especially in the microwave frequency band.

[0040] Therefore, the present invention believes that if the advantages of aluminum oxide and silicon nitride can be combined, a material having both excellent insulation and electromagnetic shielding properties can be obtained. The present invention places silicon nitride in acetamide aluminum hydroxide ionic liquid, and allows a sufficient amount of aluminum hydroxide to be effectively attached to the surface of silicon nitride under ultrasonic stirring, and then adjusts the appropriate heating rate so that the aluminum hydroxide on the surface of silicon nitride is oxidized to aluminum oxide, and minimizes the effect of the oxidation process on silicon nitride, thereby obtaining an aluminum oxide / silicon nitride material having excellent insulation and electromagnetic shielding properties. However, the present invention finds that the aluminum oxide / silicon nitride material obtained by the present invention has poor dispersibility in polyvinyl chloride resin. Therefore, the present invention further uses polydopamine to coat the aluminum oxide / silicon nitride material to obtain a polydopamine-coated aluminum oxide / silicon nitride, which has better compatibility with polyethylene resin and is more evenly dispersed in polyethylene resin.

[0041] The present invention mixes the prepared polydopamine-coated alumina / silicon nitride with polyvinyl chloride resin in an appropriate proportion to obtain an insulating material with excellent insulation and electromagnetic shielding properties. The insulating material can be applied to the insulation layer of the high-voltage wire harness of new energy vehicles. Compared with the traditional structure of two insulating layers and one shielding layer of the high-voltage wire harness of new energy vehicles, the high-voltage wire harness prepared by the present invention greatly simplifies the wire harness structure and shortens the process flow while ensuring the insulation and electromagnetic shielding properties. It is the future development direction of the high-voltage wire harness of new energy vehicles.

[0042] In addition, due to the presence of polydopamine-coated alumina / silicon nitride, alumina and silicon nitride are not easy to burn at high temperatures and have a high melting point and thermal stability. The high-voltage wire harness for new energy vehicles prepared by the present invention also has excellent flame retardant properties.

[0043] Beneficial effects of the present invention:

[0044] The present invention uses silicon nitride, acetamide aluminum hydroxide ionic liquid, and dopamine hydrochloride as raw materials to prepare polydopamine-coated alumina / silicon nitride with excellent insulation and electromagnetic shielding properties, and applies it to the high-voltage wire harness insulation layer of new energy vehicles. Compared with the traditional new energy vehicle high-voltage wire harness structure with two insulating layers and one shielding layer, the high-voltage wire harness prepared by the present invention greatly simplifies the wire harness structure and shortens the process flow while ensuring insulation and electromagnetic shielding properties, and is the future development direction of high-voltage wire harnesses for new energy vehicles. DETAILED DESCRIPTION

[0045] Polyvinyl chloride resin: Model: SG-5, Zhengzhou Xigui Chemical Co., Ltd.

[0046] Silicon nitride: particle size: 15 μm, model: XT-SI3N4-7, Shanghai Xiangtian Nanomaterials Co., Ltd.

[0047] Alumina: particle size: 6-12 microns, model: DCS-0800E, Dongguan Dongchao New Material Technology Co., Ltd.

[0048] Example 1

[0049] A method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following steps: mixing 100 parts of polyvinyl chloride resin and 3 parts of polydopamine-coated aluminum oxide / silicon nitride by mass, granulating the mixture in a twin-screw extruder to obtain an insulating layer material; and coating the insulating layer material on the outside of a wire core by a conventional process to form an insulating layer to obtain the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0050] The thickness of the insulating layer is 5 mm.

[0051] The temperature of the feeding zone of the twin-screw extruder is 120°C; the temperature of the middle zone is 175°C; and the temperature of the discharging zone is 165°C.

[0052] A method for preparing polydopamine-coated aluminum oxide / silicon nitride comprises the following steps:

[0053] S1: Mix 5 parts of acetamide and 20 parts of anhydrous aluminum chloride by mass, and stir until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid;

[0054] S2: adding 14 parts by mass of silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating for 10 minutes, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0055] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2, raising the temperature from room temperature to 110°C at 2°C / min, then raising the temperature to 550°C at 10°C / min, oxidizing at a constant temperature for 40 minutes, and finally cooling naturally to room temperature to obtain aluminum oxide / silicon nitride;

[0056] S4: Mix 2 parts of dopamine hydrochloride and 300 parts of water by mass and stir until the dopamine hydrochloride is dissolved to obtain an aqueous solution of dopamine hydrochloride, then add 6 parts of the aluminum oxide / silicon nitride obtained in step S3, and adjust the pH to 8 with 8wt% tris(hydroxymethyl)aminomethane aqueous solution, stir for 30 minutes, and finally, centrifuge and dry to obtain the polydopamine-coated aluminum oxide / silicon nitride.

[0057] The ultrasonic frequency is 40KHz and the power is 350W.

[0058] Example 2

[0059] The difference from Example 1 is that the heating rate of step S3 in the preparation method of polydopamine-coated aluminum oxide / silicon nitride is different.

[0060] A method for preparing polydopamine-coated aluminum oxide / silicon nitride comprises the following steps:

[0061] S1: Mix 5 parts of acetamide and 20 parts of anhydrous aluminum chloride by mass, and stir until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid;

[0062] S2: adding 14 parts by mass of silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating for 10 minutes, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0063] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2, raising the temperature from room temperature to 550° C. at a rate of 10° C. / min, oxidizing at a constant temperature for 40 min, and finally cooling naturally to room temperature to obtain aluminum oxide / silicon nitride;

[0064] S4: Mix 2 parts of dopamine hydrochloride and 300 parts of water by mass and stir until the dopamine hydrochloride is dissolved to obtain an aqueous solution of dopamine hydrochloride, then add 6 parts of the aluminum oxide / silicon nitride obtained in step S3, and adjust the pH to 8 with 8wt% tris(hydroxymethyl)aminomethane aqueous solution, stir for 30 minutes, and finally, centrifuge and dry to obtain the polydopamine-coated aluminum oxide / silicon nitride.

[0065] The ultrasonic frequency is 40KHz and the power is 350W.

[0066] Example 3

[0067] The difference from Example 1 is that aluminum oxide / silicon nitride is used to replace the aluminum oxide / silicon nitride coated with polydopamine.

[0068] A method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following steps: mixing 100 parts of polyvinyl chloride resin and 3 parts of aluminum oxide / silicon nitride by mass, granulating the mixture in a twin-screw extruder to obtain an insulating layer material; and coating the insulating layer material on the outside of a wire core by conventional processes to form an insulating layer to obtain the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0069] The thickness of the insulating layer is 5 mm.

[0070] The temperature of the feeding zone of the twin-screw extruder is 120°C; the temperature of the middle zone is 175°C; and the temperature of the discharging zone is 165°C.

[0071] A method for preparing aluminum oxide / silicon nitride comprises the following steps:

[0072] S1: Mix 5 parts of acetamide and 20 parts of anhydrous aluminum chloride by mass, and stir until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid;

[0073] S2: adding 14 parts by mass of silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating for 10 minutes, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0074] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2, raising the temperature from room temperature to 110°C at 2°C / min, then raising the temperature to 550°C at 10°C / min, oxidizing at a constant temperature for 40 minutes, and finally naturally cooling to room temperature to obtain aluminum oxide / silicon nitride.

[0075] The ultrasonic frequency is 40KHz and the power is 350W.

[0076] Example 4

[0077] The difference from Example 3 is that a mixture of aluminum oxide and silicon nitride is used to replace aluminum oxide / silicon nitride.

[0078] A method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following steps: mixing 100 parts of polyvinyl chloride resin, 1 part of aluminum oxide, and 2 parts of silicon nitride by mass, and granulating the mixture in a twin-screw extruder to obtain an insulating layer material; and coating the insulating layer material on the outside of a wire core by conventional processes to form an insulating layer to obtain the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0079] The thickness of the insulating layer is 5 mm.

[0080] The temperature of the feeding zone of the twin-screw extruder is 120°C; the temperature of the middle zone is 175°C; and the temperature of the discharging zone is 165°C.

[0081] Comparative Example 1

[0082] The difference from Example 1 is that aluminum oxide is used to replace the aluminum oxide / silicon nitride coated with polydopamine.

[0083] A method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following steps: mixing 100 parts of polyvinyl chloride resin and 3 parts of aluminum oxide by mass, granulating the mixture in a twin-screw extruder to obtain an insulating layer material; and coating the insulating layer material on the outside of a wire core by conventional processes to form an insulating layer to obtain the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0084] The thickness of the insulating layer is 5 mm.

[0085] The temperature of the feeding zone of the twin-screw extruder is 120°C; the temperature of the middle zone is 175°C; and the temperature of the discharging zone is 165°C.

[0086] Comparative Example 2

[0087] The difference from Example 1 is that silicon nitride is used to replace the polydopamine-coated aluminum oxide / silicon nitride.

[0088] A method for preparing a photovoltaic energy storage high-voltage wire harness with high flame retardancy comprises the following steps: mixing 100 parts of polyvinyl chloride resin and 3 parts of silicon nitride by mass, granulating the mixture in a twin-screw extruder to obtain an insulating layer material; and coating the insulating layer material on the outside of a wire core by conventional processes to form an insulating layer to obtain the photovoltaic energy storage high-voltage wire harness with high flame retardancy.

[0089] The thickness of the insulating layer is 5 mm.

[0090] The temperature of the feeding zone of the twin-screw extruder is 120°C; the temperature of the middle zone is 175°C; and the temperature of the discharging zone is 165°C.

[0091] Comparative Example 3

[0092] The difference from Example 1 is that in the preparation method of polydopamine-coated aluminum oxide / silicon nitride, an aluminum chloride aqueous solution is prepared in step S1.

[0093] A method for preparing polydopamine-coated aluminum oxide / silicon nitride comprises the following steps:

[0094] S1, by mass, mixing 10 parts of water with 5 parts of anhydrous aluminum chloride, stirring until the anhydrous aluminum chloride is dissolved, to obtain an aluminum chloride aqueous solution;

[0095] S2: adding 14 parts by mass of silicon nitride to the aluminum chloride aqueous solution obtained in step S1, stirring and ultrasonicating for 10 minutes, and then centrifuging to obtain aluminum ion-loaded silicon nitride;

[0096] S3 heats the aluminum ion-loaded silicon nitride obtained in step S2, raising the temperature from room temperature to 110°C at 2°C / min, then raising the temperature to 550°C at 10°C / min, oxidizing at a constant temperature for 40 minutes, and finally cooling naturally to room temperature to obtain aluminum oxide / silicon nitride;

[0097] S4: Mix 2 parts of dopamine hydrochloride and 300 parts of water by mass and stir until the dopamine hydrochloride is dissolved to obtain an aqueous solution of dopamine hydrochloride, then add 6 parts of the aluminum oxide / silicon nitride obtained in step S3, and adjust the pH to 8 with 8wt% tris(hydroxymethyl)aminomethane aqueous solution, stir for 30 minutes, and finally, centrifuge and dry to obtain the polydopamine-coated aluminum oxide / silicon nitride.

[0098] The ultrasonic frequency is 40KHz and the power is 350W.

[0099] Test Example 1:

[0100] Electromagnetic shielding performance test:

[0101] Refer to GB / T 30142-2013 "Measurement method for shielding effectiveness of planar electromagnetic shielding materials", instrument: De Technology (N5224A) network analyzer; sample is insulating layer material: 20mm×10mm×2mm.

[0102] Table 1: Electromagnetic shielding performance test results

[0103] Shielding performance / % Example 1 82.4 Example 2 74.3 Example 3 76.9 Example 4 62.2 Comparative Example 1 52.1 Comparative Example 2 57.6 Comparative Example 3 72.9

[0104] Test Example 2

[0105] Volume resistivity test:

[0106] Refer to GB / T 15662-1995 "Test method for volume resistivity of conductive and antistatic plastics"; the sample is an insulating layer material: diameter × thickness = 100mm × 5mm.

[0107] Table 2: Volume resistivity test results

[0108] <![CDATA[Volume resistivity (10 14 Ω·cm) <!-- 6 -->]]> Example 1 12.7 Example 3 10.3

[0109] It can be seen from Table 1 that the insulating layer material of Example 1 of the present invention has the strongest electromagnetic shielding performance, which uses polydopamine-coated aluminum oxide / silicon nitride as an additive. Silicon nitride is a ceramic material with excellent thermal conductivity and mechanical properties, and it has certain potential in high-frequency electromagnetic shielding. Silicon nitride has a high dielectric constant and low dielectric loss, and can effectively absorb and scatter high-frequency electromagnetic waves. Aluminum oxide is a commonly used ceramic material with excellent mechanical properties and chemical stability. Although the dielectric constant of aluminum oxide is relatively low, it can still be used for high-frequency electromagnetic shielding, especially in the microwave frequency band. The shielding effect is better. Polydopamine and polyethylene resin have better compatibility, which can make the polydopamine-coated aluminum oxide / silicon nitride dispersed more evenly in the polyethylene resin. The combination of the three greatly enhances the electromagnetic shielding performance of the material.

[0110] Compared with Example 1, the preparation step S3 of the polydopamine-coated aluminum oxide / silicon nitride in the preparation scheme of Example 2 did not control the initial heating rate, resulting in the electromagnetic shielding performance of the obtained insulating layer material being lower than that of Example 1. The present invention believes that this is because the slower initial heating rate is conducive to the volatilization of acetamide on the surface of silicon nitride and the slow oxidation of aluminum hydroxide on the surface to form a protective layer on the surface of silicon nitride, effectively preventing the oxidation of silicon nitride. The present invention speculates that this is conducive to improving the electromagnetic shielding performance of the material.

[0111] Compared with Example 1, Example 3 does not coat the aluminum oxide / silicon nitride with polydopamine, and the electromagnetic shielding performance of the obtained insulating layer material is also reduced. The present invention believes that this is due to the poor dispersibility of the aluminum oxide / silicon nitride material in the polyvinyl chloride resin.

[0112] Compared with Example 3, Example 4 uses a mixture of aluminum oxide and silicon nitride to replace aluminum oxide / silicon nitride, Comparative Example 1 uses aluminum oxide to replace polydopamine-coated aluminum oxide / silicon nitride, and Comparative Example 2 uses silicon nitride to replace polydopamine-coated aluminum oxide / silicon nitride, all of which lead to a decrease in electromagnetic shielding performance, which further proves that polydopamine-coated aluminum oxide / silicon nitride has better electromagnetic shielding performance.

[0113] In Comparative Example 3, the present invention replaces the acetamide aluminum hydroxide ionic liquid with an aluminum chloride aqueous solution, and the electromagnetic shielding performance of the obtained insulating material is also not as good as that of Example 1. The present invention believes that this is because the aluminum ions in the acetamide aluminum hydroxide ionic liquid are more easily adsorbed on the silicon nitride surface, and are more easily oxidized in the air than simple aluminum ions.

[0114] It can also be seen from Table 2 that compared with aluminum oxide / silicon nitride, the insulating material obtained by using polydopamine-coated aluminum oxide / silicon nitride as an additive has a higher volume resistivity. The present invention believes that this is because the aluminum oxide / silicon nitride coated with polydopamine has better dispersibility in polyvinyl chloride resin.

[0115] The present invention mixes the prepared polydopamine-coated alumina / silicon nitride with polyvinyl chloride resin in an appropriate proportion to obtain an insulating material with excellent insulation and electromagnetic shielding properties. The insulating material can be applied to the insulation layer of the high-voltage wire harness of new energy vehicles. Compared with the traditional structure of two insulating layers and one shielding layer of the high-voltage wire harness of new energy vehicles, the high-voltage wire harness prepared by the present invention greatly simplifies the wire harness structure and shortens the process flow while ensuring the insulation and electromagnetic shielding properties. It is the future development direction of the high-voltage wire harness of new energy vehicles.

[0116] Of course, the above description is only a specific embodiment of the present invention and is not intended to limit the scope of implementation of the present invention. All equivalent changes or modifications made according to the structure, characteristics and principles described in the patent application scope of the present invention should be included in the patent application scope of the present invention.

Claims

1. A photovoltaic energy storage high-voltage wire harness with flame retardant properties, characterized in that: Including wire core and insulation layer; by mass, the insulation layer includes the following raw materials: 100 parts of polyvinyl chloride resin; 1-10 parts of polydopamine coated aluminum oxide / silicon nitride; The preparation method of the polydopamine-coated aluminum oxide / silicon nitride comprises the following steps: S1: mixing acetamide and anhydrous aluminum chloride and stirring until the anhydrous aluminum chloride is dissolved to obtain acetamide aluminum hydroxide ionic liquid; S2: adding silicon nitride to the acetamide aluminum hydroxide ionic liquid prepared in step S1, stirring and ultrasonicating, and then centrifuging to obtain aluminum ion-loaded silicon nitride; S3 heats the aluminum ion-loaded silicon nitride obtained in step S2 to obtain aluminum oxide / silicon nitride; S4: mixing dopamine hydrochloride and water and stirring until the dopamine hydrochloride is dissolved to obtain a dopamine hydrochloride aqueous solution, adding the aluminum oxide / silicon nitride obtained in step S3, and adjusting the pH with a tris(hydroxymethyl)aminomethane aqueous solution, and finally stirring, centrifuging, and drying to obtain the polydopamine-coated aluminum oxide / silicon nitride; The specific steps of the heating treatment in step S3 are: heating from room temperature to 100-120°C at 1-3°C / min, then heating to 500-600°C at 10-15°C / min, oxidizing at a constant temperature for 30-60 minutes, and finally cooling naturally to room temperature.

2. The flame retardant photovoltaic energy storage high voltage wire harness according to claim 1, characterized in that: The ultrasonic frequency in step S2 is 30-50KHz, and the power is 300-400W.

3. The flame retardant photovoltaic energy storage high voltage wire harness according to claim 1, characterized in that: The concentration of the tris(hydroxymethyl)aminomethane aqueous solution in step S4 is 7-8wt%.

4. A method for preparing a photovoltaic energy storage high-voltage wire harness with flame retardant properties as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The polyvinyl chloride resin and the polydopamine-coated alumina / silicon nitride are mixed and granulated in a twin-screw extruder to obtain an insulating layer material; The insulating layer material is coated on the outside of the wire core to form an insulating layer, thereby obtaining the photovoltaic energy storage high-voltage wire harness with flame retardant properties.

5. The method for preparing the flame-retardant photovoltaic energy storage high-voltage wire harness according to claim 4, characterized in that: The temperature of the feeding zone of the twin-screw extruder is 120-130°C; the temperature of the middle zone is 170-180°C; and the temperature of the discharging zone is 160-170°C.

Citation Information

Patent Citations

  • Preparation method of biomass carbon-based ultralight insulating electromagnetic shielding material

    CN115612250A

  • High-speed extrusion flame-retardant PVC high-wiring-harness material and preparation method thereof

    CN111690213A

  • Flame-retardant PVC material and preparation method thereof

    CN114044991A